Clinical Utility of Bile Duct Axis Deviation for Differential Diagnosis Between Pancreatic Head Cancer and Bile Duct Cancer. Issue 4 (April 2021) - Shirakawa, Toru; Tomimaru, Yoshito; Hayashi, Shiro; Noguchi, Kozo; Nishida, Tsutomu; Dono, Keizo
Backgrounds: Differential diagnosis between pancreatic head cancer (PHC) and intrapancreatic bile duct cancer (BDC) is important, but no clinical standard has been established. Here we examine the diagnostic utility of bile duct axis deviation and other clinical factors for this differential diagnosis. Methods: This study enrolled patients who underwent pancreaticoduodenectomy for PHC or BDC at our center between 2009 and 2016. PHCs in groove or uncinate portions were excluded from analysis. From contrast-enhanced computed tomography images, the bile duct angle (BDA) was measured using three points: the junction of intrahepatic bile ducts, upper pancreatic edge, and Vater papilla. Logistic regression was performed to evaluate the diagnostic performance of BDA and other clinical factors for differential diagnosis. Results: During the study period, 22 PHCs and 31 BDCs were resected. The combination of BDA ≤ 130°, main pancreatic duct diameter ≥ 4.3 mm, and absence of jaundice predicted PHC rather than BDC with an area under the curve of the receiver-operator characteristics curve of .856 (95% confidence interval, .766-.947). Conclusion: Clinical findings of larger bile duct axis deviation, main pancreatic duct dilation, and the absence of jaundice may be useful for distinguishing PHC from BDC.